NIR photoresponsive crosslinked upconverting nanocarriers toward selective intracellular drug release - Yang, Yanmei (2014)
An NIR-responsive mesoporous silica coated upconverting nanoparticle (UCNP) conjugate is developed for controllable drug delivery and fluorescence imaging in living cells. In this work, antitumor drug doxorubicin (Dox) molecules are encapsulated within cross-linked photocaged mesoporous silica coated UCNPs. Upon 980 nm light irradiation, Dox could be selectively released through the photocleavage of theo-nitrobenzyl (NB) caged linker by the converted UV emission from UCNPs. This NIR light-responsive nanoparticle conjugate demonstrates high efficiency for the controlled release of the drug in cancer cells. Upon functionalization of the nanocarrier with folic acid (FA), this photocaged FA-conjugated silica-UCNP nanocarrier will also allow targeted intracellular drug delivery and selective fluorescence imaging towards the cell lines with high level expression of folate receptor (FR).